Urbanization causes shifts in the functional traits and foraging activity, and alters food particle size preference and biomass removal of urban-dwelling ants - Chen, Yuan-Hung; Neoh, Kok-Boon (Frontiers in Ecology and Evolution, 2023)
Urbanization may lead to changes in assemblage and result in shifts in trait distribution from natural habitats to highly urbanized habitats. The shift in functional traits can affect ecosystem functions in urban areas. This study explored the foraging period of ants over 72 h and determined the relationship between the behavioral, morphological, and physiological traits of local foragers ants and environmental conditions in urban and forest sites. In addition, this study examined the ants’ ecosystem functions and compared it with that of their forest counterparts. Our results revealed that the foraging period of ants (i.e., Cardiocondyla sp.1, Monomorium chinense, Paratrechina longicornis, Pheidole megacephala, and Solenopsis sp.1) in urban areas peaked between 0900 and 1500 and that of some ants (i.e., Carebara diversa, P. megacephala, Pheidole fervens, Plagiolepis longwang, and Nylanderia sp.1) in forest areas was constant over time. For urban ants, a weak correlation was observed between foraging period and body size traits (i.e., Weber’s length and head width). This finding indicates that the major factor underlying the change in the foraging period might not be related to body size. Rather, the change may be attributed to synchronization between food availability and human activity (waste disposal; i.e., between 0900 and 1800). The shift in the functional traits of ants affects ecosystem functions in urban areas. In urban areas, although only one predatory ant species (P. megacephala) was sampled, its activity density was high. Most of these individuals were active during the daytime, indicating that the predatory behavior of ants in the novel urban environment has decreased temporally and is limited to the daytime. Urban ants tended to choose smaller food particles, whereas forest ants preferred larger food particles and had a twofold higher food removal rate.